2022
DOI: 10.1186/s13567-022-01052-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and public health implications for environmental exposure to Chlamydia abortus: from enzootic to zoonotic disease

Abstract: Environmental transmission of Chlamydia abortus as a result of enzootic disease or disease outbreaks and the threats posed by this pathogen has been previously reported, however a state-of-the-science review of these reports and the identification of future research priorities in this area is still lacking. This study provides an overview of the current knowledge of host–pathogen–environment interactions, addressing public health risks and identifying critical questions and research gaps. We performed a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 172 publications
(195 reference statements)
3
34
0
3
Order By: Relevance
“…26 The bacteria infect trophoblasts, causing damage, as well as inducing placentitis, vasculitis, and thrombosis. 26 The combined effects of these outcomes reduce fetoplacental exchange and ultimately cause abortion. 26 Placentitis, vasculitis, and rare thrombosis, similar to ovine cases of C. abortus, were reported in cases of C. psittaci equine abortions in Australia 6 ; the authors identified a characteristic lymphohistiocytic placentitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The bacteria infect trophoblasts, causing damage, as well as inducing placentitis, vasculitis, and thrombosis. 26 The combined effects of these outcomes reduce fetoplacental exchange and ultimately cause abortion. 26 Placentitis, vasculitis, and rare thrombosis, similar to ovine cases of C. abortus, were reported in cases of C. psittaci equine abortions in Australia 6 ; the authors identified a characteristic lymphohistiocytic placentitis.…”
Section: Discussionmentioning
confidence: 99%
“…26 The combined effects of these outcomes reduce fetoplacental exchange and ultimately cause abortion. 26 Placentitis, vasculitis, and rare thrombosis, similar to ovine cases of C. abortus, were reported in cases of C. psittaci equine abortions in Australia 6 ; the authors identified a characteristic lymphohistiocytic placentitis. 6 Similar findings were reported in C. psittaci abortions in Hungary in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…17 Eine Zoonosegefahr besteht vor allem für schwangere Frauen, welche direkten oder indirekten Kontakt zu infizierten Kleinwiederkäuern sowie Totgeburten und Abortmaterial (Plazenta, Lochialflüssigkeit, Fötus) haben. 102 C. abortus-induzierte schwere Allgemeinerkrankungen und Aborte bei schwangeren Frauen nach Kontakt zu Schaf-und seltener Ziegenaborten sind mehrfach in der Schweiz und Europa beschrieben. 14,69,102 Kürzlich konnte bei einer schwangeren Frau mit SARS-CoV2-negativer Pneumonie ebenfalls C. abortus nachgewiesen werden.…”
Section: Chlamydia Abortusunclassified
“…102 C. abortus-induzierte schwere Allgemeinerkrankungen und Aborte bei schwangeren Frauen nach Kontakt zu Schaf-und seltener Ziegenaborten sind mehrfach in der Schweiz und Europa beschrieben. 14,69,102 Kürzlich konnte bei einer schwangeren Frau mit SARS-CoV2-negativer Pneumonie ebenfalls C. abortus nachgewiesen werden. 46 Diese Patientin erlitt glücklicherweise keinen Abort, hatte aber anamnestisch ebenfalls Kontakt zu einer Schaf-und Ziegenhaltung mit Abortproblemen.…”
Section: Chlamydia Abortusunclassified
“…Significantly, Chlamydia trachomatis is the number one sexually transmitted bacterial pathogen globally, and also is a major cause of preventable blindness in developing countries (47)(48)(49), and C. pneumoniae is a common respiratory pathogen (50)(51)(52)(53)(54). Several animal Chlamydia species are zoonotic pathogens (55)(56)(57)(58)(59)(60)(61)(62)(63)(64). Waddlia chondrophila is one of several Chlamydia-like organisms, termed environmental chlamydiae, typically found in lower eukaryotes, such as amoebae, but can infect, and induce abortion in, vertebrates, including humans (65).…”
Section: Introductionmentioning
confidence: 99%